The correlation between the level of secretion and the type of monoclonal paraprotein and kidney damage in lymphoproliferative disorders (Russian Medical and Social Journal, 2019)
Introduction. The course of lymphoproliferative diseases accompanied by the secretion of paraproteins is complicated by damage to the kidneys and the development of renal failure. There is a pathogenetic relationship between the physicochemical properties of monoclonal proteins and renal pathology.Objective: to find out the relationship between the type of monoclonal paraprotein, the level of its secretion and the degree of renal failure in lymphoproliferative diseases.Patients and methods. We analyzed 108 patients with lymphoproliferative diseases in whom secretion of paraprotein was detected. Age from 31 to 86 years (median 62.5 years). Chronic kidney disease (CKD) was diagnosed in 78 out of 108 patients.Results. CKD was diagnosed in patients with multiple myeloma. Stage III CKD was diagnosed in 28 (35.9%) patients, stage IV - in 14 (17.9%), stage V - in 19 (24.4%). 91 patients were diagnosed with concomitant diseases predisposing to the development of renal pathology. In the blood serum of patients with paraproteinemic hemoblastosis in combination with CKD, the vast majority were patients with the secretion of Gκ and Gλ paraproteins, free light chains (FLC). In a significant number of patients, Bens-Jones protein (BJ) in urine was determined. Less commonly, the secretion of paraproteins Dλ, Aλ, Aκ and Mκ was determined. The highest level of pathological proteins of all classes and their structural components and fragments was observed in patients with stage III CKD. A negative correlation of glomerular filtration rate (GFR) with FLCκ in the blood (r = –0.21), GFR with BJκ (r = –0.35), GFR with FLCλ in the blood (r = –0.13), GFR c BJλ, which indicates a tendency to damage the kidneys of FLC and protein BJ.Conclusion. In patients with lymphoproliferative diseases accompanied by monoclonal secretion of paraprotein and kidney damage with the development of CKD, in most cases the blood paraproteins Gκ, Gλ, FLCκ and FLCλ as well as protein BJ in urine, were determined. Paraproteins Aκ, Aλ, Mκ, Mλ, Dλ were determined much less frequently in serum. The highest level of pathological Ig and their structural components was observed in patients with stage III CKD. No association with quantitative level, type of paraprotein, and kidney damage was found. The role of FLC and BJ protein in the development of nephropathy has been confirmed.
Keywords: Lymphoproliferative Disorders; Paraproteins; Bence Jones protein; Acute Kidney Injury; Chronic Kidney Disease